PSexuality in Maslow’s Hierarchy: A Cross-Sectional Study on Italian Nurses’ Competence - Emanuele Primavera; Camilla Marzolani; Serena Pignatelli; Luca Natale (Dissertation Nursing, 2025)
Background: Sexuality in patients has historically been a taboo topic within the nursing profession and is rarely discussed among practitioners. This study aimed to assess the competencies of Italian nurses regarding patients' sexuality.